PENINGKATAN LITERASI LAPORAN KEUANGAN DAN PEMASARAN DIGITAL MELALUI PELATIHAN DAN PENDAMPINGAN PADA UMKM ERZI CRAFT, PURBALINGGA - Ginanjar Adi Nugraha; Minadi Wijaya; Hendro Sukoco; Riskika Alkaromatunnisa; Dwi Indriyani (Universitas Mataram, 2026)
Limitations in financial statement literacy and digital marketing literacy remain major constraints for household MSMEs in developing their businesses sustainably. Social media and e-commerce are generally utilized merely as sales channels, rather than as integrated information systems that present sales, cost, and profit data comprehensively. This condition results in business decision-making that is not supported by adequate financial performance analysis, thereby causing opportunities for improving profitability, operational efficiency, and market expansion to remain underutilized by MSME actors. This community service program aims to enhance business actors’ understanding of financial statements and to optimize digital marketing strategies through training, mentoring, and the provision of supporting technologies. The activities were conducted in collaboration with the partner ErZi Craft in Purbalingga Regency, which operates in the handmade knitting craft industry. The implementation methods included socialization activities, financial statement literacy training, preparation of Standard Operating Procedures (SOP) and a Business Model Canvas (BMC), as well as training in branding, packaging, product photography, e-catalog development, and live streaming on Shopee and Instagram platforms. The results of the activities demonstrate a significant improvement in the partner’s business performance. The partner’s understanding of simple financial statements and Shopee financial reports increased, enabling them to prepare income statements and monitor cash flows on a regular basis. SOP and BMC documents have been developed and have begun to be used as references for daily operational activities. From the perspective of digital marketing, the partner now possesses a business logo, digital catalog designs, and more attractive photo and video promotional content. The partner is also proficient in utilizing live streaming features as a routine promotional medium, which has contributed to the expansion of market reach to various cities in Indonesia and abroad, such as Bekasi, Tangerang, Jakarta, South Sumatra, Purworejo, and even Singapore. This community service program has been proven to contribute to enhancing the partner’s business capacity through the strengthening of financial statement literacy, operational governance, and more professional digital marketing skills. Increased turnover and expanded market reach provide more stable income opportunities for business owners and members, thereby supporting the achievement of the Sustainable Development Goals (SDGs), particularly poverty reduction and women’s empowerment in productive economic activities.